Safety evaluation of the food enzyme subtilisin from the non‐genetically modified Bacillus paralicheniformis strain LMG S‐30155 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme subtilisin (serine endopeptidase, EC 3.4.21.62) is produced with the non‐genetically modified microorganism Bacillus paralicheniformis strain LMG S‐30155 by ENMEX SA de CV, now part of Kerry Food Ingredients (Cork) Ltd. The food enzyme is intended to be used in oil production, hydrolysis of vegetable/microbial/animal proteins, yeast processing and production of flavouring preparations. The production strain of the food enzyme contains known antimicrobial resistance genes and genes involved in bacitracin biosynthesis. Consequently, it does not fulfil the requirements for the QPS approach to safety assessment. Bacitracin was detected in the food enzyme and the ■■■■■ The presence of bacitracin, a medically important antimicrobial, in the food enzyme represents a risk for the development of resistance in bacteria. Due to the presence of bacitracin, the Panel concluded that the food enzyme subtilisin produced with the non‐genetically modified Bacillus paralicheniformis strain LMG S‐30155 cannot be considered safe.